Policy Implementation of The Regional Student Education And Training Center at The Youth And Sports Office of Makassar City - Muskarnain Yunus; Herman H; Muhammad Irvan Nur' Iva; Andi Anugrah Mahyuddin (International Journal Of Public Policy and Bureaucracy, 2026)
This study aims to examine and explain the implementation of the Regional Student Education and Training Center (PPLPD) policy at the Youth and Sports Office of Makassar City, as well as to identify the supporting and inhibiting factors affecting its implementation. This research employs a descriptive qualitative approach. Data were collected through observation, in-depth interviews, and documentation, while data analysis was conducted using data condensation, data display, and conclusion drawing techniques. The findings indicate that the implementation of the PPLPD policy at the Youth and Sports Office of Makassar City has not yet been fully optimal. Several aspects—namely communication, implementers’ attitudes and commitment, organizational environment, clarity of policy size and objectives, political factors, and recruitment—have been implemented effectively. This is reflected in clear program communication, professional conduct of implementers, strong stakeholder support, well-defined performance standards, neutral policy execution, and transparent and fair athlete selection mechanisms. However, challenges persist in terms of resources, bureaucratic structure, and funding. These limitations are evidenced by budget constraints, sports facilities and infrastructure that have not fully met the ideal requirements for athlete development, and the lack of consistent formal coordination mechanisms. Therefore, strengthening resource capacity, improving bureaucratic coordination structures, and increasing funding allocation are necessary to enhance the effectiveness and sustainability of the PPLPD policy implementation in improving student-athlete performance in Makassar City.